Prediction of the day of ovulation in mares through physiological parameters measured during estrous - Miro i Roig, Jordi; Muñoz, Fernando; Piedrafita, Jesús; Quintero Moreno, Armando (Revista Científica de la Facultad de Ciencias Veterinarias)
In this research, two herds of swamp and river mixed water buffaloes were observed during an eight months period (july 97- february 98) in order to find and characterize some pathologic entities in two farms at Mara municipality, Zulia state. A total of 469 water buffaloes were periodically observed. Forty two (42) visits on a weekly schedule were realized and data about clinical cases as well as blood, serum and fecal samples for analysis were collected. Biopsies and necropsies were performed and tissue samples were processed for pathologic evaluation. Anamnesis of each case was done and mortality and morbidity rates were recorded. There were 105 clinical cases (68 young and 37 adults) of varied pathological nature from which biopsies (12) were taken. During the observational period, there were five (5) dead animals for necropsy from which samples were taken and histopathologically evaluated. All collected cases were diagnosed, medical treatments were applied and the pathological entities were characterized. Among them, there were nutritional problems, parasitic diseases, traumas, viral and bacterial diseases as well as genetic problems. In this work a relation of pathologic cases is reported as well as the nature of pathologic entities.